PENGARUH SERTIFIKASI DALAM PENINGKATAN PROFESIONALISME GURU ANAK SEKOLAH DASAR (SD) - yono, sri (Trapsila: Jurnal Pendidikan Dasar, 2020)
Law Number 14 of 2005 concerning Teachers and Lecturers defines that professionalism is a job or activity carried out by a person and becomes a source of life income that requires expertise, proficiency or skills that meet certain quality standards or norms and require professional education. The recognition of the teacher's position as a professional is proven by an educator certificate. As professionals, teachers are expected to increase their dignity and role as agents of learning. Teacher certification as an effort to improve teacher quality is expected to improve the quality of learning and the quality of education in Indonesia in a sustainable manner. Teacher professionalism is often associated with three important factors, namely competence, certification, and professional allowances. These three factors are predicted to affect the quality of education. The purpose of writing this paper is to determine the effect of certification on increasing teacher professionalism. Certification is closely related to the learning process, so that it cannot be assumed to reflect superior competencies throughout life. Post-certification should be the initial milestone for teachers to continuously improve competence and professionalism. Prescriptively, management competency support, empowerment strategies, development supervision, and continuous professional development are alternative theoretical dimensions to improve teacher competence and professionalism. The four theoretical dimensions are based on the humanistic philosophy, that basically teachers can increase their professionalism independently. These theoretical dimensions serve as facilities and a platform for teachers to increase commitment and awareness based on self-reflection in order to improve their professionalism.